Development of Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) in tomato genotypes - Dalbianco, Alessandro Bandeira [UNESP]; de Lima Alvarez, Daniel [UNESP]; da Silva, Nadja Nara Pereira [UNESP]; Daniel, Diego Fernando; Santos, Daniel Mariano [UNESP]; Júnior, Santino Seabra; de Oliveira, Regiane Cristina [UNESP] (Lepidus Tecnologia, 2025)
Tomato plants are the most widely cultivated fruit vegetables globally. The tomato leaf miner (Tuta absoluta) is the leading pest of this crop and can cause up to 100% loss of production. Therefore, the aim was to evaluate the development and resistance of antibiosis and non-preference types (antixenosis) for oviposition and feeding of T. absoluta in commercial tomato hybrids in choice and no-choice tests. For the experiments, an open-pollinated tomato cultivar was used as a control: ‘Santa Clara’ cultivar - susceptible - Italian type, along with eight commercial tomato hybrids were used: ‘Compack’ - salad type, ‘Caniati’ - Italian type, ‘Grazianni’ - Italian type, ‘Sweet Heaven’ - grape type, ‘Cascade’ - cherry type, ‘Ellen’ - salad type, ‘Bento’ - Italian type, and ‘Dominador’ - salad type, all having an indeterminate growth habit. According to the evaluated biological parameters (dendrogram and principal component analysis - PCA), the ‘Sweet Heaven’ hybrid showed a negative effect on the development of T. absoluta, with an increase in the duration of the larval, adult, and total phases, and low larval and total viability. The tomato hybrid ‘Cascade’ exhibited lower attractiveness for T. absoluta oviposition in no-choice tests. The tomato hybrids ‘Sweet Heaven’, ‘Compack’, and ‘Cascade’ showed a lower percentage of leaf area consumed. However, ‘Dominador’, ‘Santa Clara’, and ‘Ellen’ were the tomato genotypes that showed higher susceptibility to the development of T. absoluta, encompassing high larval, pupal, and total viability (larva-adult period). Concluding that the ‘Sweet Heaven’ hybrid negatively affected the development cycle of T. absoluta, while the ‘Cascade’ hybrid exhibited lower attractiveness for oviposition.
Keywords: antibiosis; antixenosis; plant resistance; Solanum lycopersicum L.; tomato leaf miner